Pinch1 is required for normal development of cranial and cardiac neural crest-derived structures. - Liang, X; Sun, Y; Schneider, J; Ding, J; Cheng, H; Ye, M; Bhattacharya, S; Rearden, A; Evans, S; Chen, J (2007)
Pinch1, an adaptor protein composed of 5 LIM domains, has been suggested to play an important role in multiple cellular processes. We found that Pinch1 is highly expressed in neural crest cells and their derivatives. To examine the requirement for Pinch1 in neural crest development, we generated neural crest conditional Pinch1 knockout mice using the Wnt1-Cre/loxP system. Neural crest conditional Pinch1 mutant embryos die perinatally from severe cardiovascular defects with an unusual aneurysmal common arterial trunk. Pinch1 mutants also exhibit multiple deficiencies in cranial neural crest-derived structures. Fate mapping demonstrated that initial migration of neural crest cells to the pharyngeal arch region occurs normally in the mutant embryos. However, in the cardiac outflow tract of mutants, neural crest cells exhibited hyperplasia and failed to differentiate into smooth muscle. Markedly increased apoptosis is observed in outflow tract cushions of mutants between embryonic days 11.5 and 13.5, likely contributing to the observed defects in cushion/valve remodeling and ventricular septation. Expression of transforming growth factor-beta(2), which plays a crucial role in outflow tract development, was decreased or absent in the outflow tract of the mutants. The decrease in transforming growth factor-beta(2) expression preceded neural crest cell death. Together, our results demonstrate that Pinch1 plays an essential role in neural crest development, perhaps in part through transforming growth factor-beta signaling.